2011
DOI: 10.1111/j.2042-7158.2010.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of commercially available nutraceutical supplements and food sources

Abstract: Objectives Nutraceuticals are components of dietary origin, with claimed beneficial therapeutic activities. The quality of nutraceuticals is paramount for efficacy and safety, and it includes quality of raw materials, different available chemical forms, complex products, lack of substitution of inappropriate materials, and the absence of contaminants. The aim of this review is to investigate the extent of substandard formulated and raw material nutraceuticals, and to highlight any consequent health concern. Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 64 publications
0
21
0
3
Order By: Relevance
“…With a reported market value of US$ 75 billion, this industry is becoming progressively popular, partly due to the public's perception that “natural is better” [6]. Joining a long list of nutraceuticals are the tocotrienols, a constituent of vitamin E found in palm oil as a phytonutrient [7].…”
Section: Introductionmentioning
confidence: 99%
“…With a reported market value of US$ 75 billion, this industry is becoming progressively popular, partly due to the public's perception that “natural is better” [6]. Joining a long list of nutraceuticals are the tocotrienols, a constituent of vitamin E found in palm oil as a phytonutrient [7].…”
Section: Introductionmentioning
confidence: 99%
“…In literature, determination of the TPC and to lesser extent FRSA have been reported for evaluation of the quality of nutraceuticals containing polyphenolic compounds (Bernal and others ). However, in depth assessment of the stability of nutraceuticals containing polyphenolic products has not been thoroughly explored (Scalia and others ; Abd‐ElSalam and others ) and very few reports investigated the significance of product quality on biological activity and safety (Lockwood ).…”
Section: Discussionmentioning
confidence: 99%
“…With all these beneficial effects, requirements for registration of GT nutraceutical products are not as demanding as those of pharmaceuticals (Bernal and others ) that lead to the presence of substandard nutraceuticals in the market. Taking in consideration that consumption of nutraceuticals is not regulated by a physician and is a lifelong habit for many of us and the complex nature of nutraceutical preparations, it has been recommended that the quality and stability of such products should be investigated carefully (Lockwood ; Abd‐ElSalam and others ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a survey carried out in the Eastern Washington Region of U.S.A. tested 13 products (7 tablet and 6 capsule formulations) by HPLC and showed that only 4 of the 13 products contained the minimum of 90% isoflavone content claimed on the label and variations in composition over time were noted [392]. Interestingly, a recent review shows that overall, most commercially available nutraceuticals are poor in quality [393].…”
Section: Sources Of Soymentioning
confidence: 99%